Variaciones sociológicas sobre la desigualdad educativa en la Argentina reciente - Leivas, Marcela; M. Lafuente, Patricio (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
The purpose is to build an update on the issue of educational inequality in the Argentinean formal education system. To that effect, thisarticle will try to take the form of a network of key concepts developed by various national experts in the field of educational research. Special attention to authors and authors that have occurred during the second half of the twenty century to the present will be provided.
Keywords: Inequality; Education; State; Art; Argentina